The Natural History of Inherited Retinal Dystrophy Due to Biallelic Mutations in the RPE65 Gene - CHUNG, DANIEL C. (Am J Ophthalmol, 2018)
• PURPOSE: To delineate the natural history of visual parameters over time in individuals with biallelic RPE65 mutation–associated inherited retinal dystrophy (IRD); describe the range of causative mutations; determine potential genotype/phenotype relationships; and describe the variety of clinical diagnoses. • DESIGN: Global, multicenter, retrospective chart review. • METHODS: STUDY POPULATION: Seventy individuals with biallelic RPE65 mutation–associated IRD. PROCEDURES: Data were extracted from patient charts. MEASUREMENTS: Visual acuity (VA), Goldmann visual field (GVF), optical coherence tomography, color vision testing, light sensitivity testing, and electroretinograms (retinal imaging and fundus photography were collected and analyzed when available). • RESULTS: VA decreased with age in a nonlinear, positive-acceleration relationship (P < .001). GVF decreased with age (P < .0001 for both V4e and III4e), with faster GVF decrease for III4e stimulus vs V4e (P = .0114, left eye; P = .0076, right eye). On average, a 1-year increase in age decreased III4e GVF by ~25 sum total degrees in each eye while V4e GVF decreased by ~37 sum total degrees in each eye, although individual variability was observed. A total of 78 clinical diagnoses and 56 unique RPE65 mutations were recorded, without discernible RPE65 mutation genotype/phenotype relationships. • CONCLUSIONS: The number of clinical diagnoses and lack of a consistent RPE65 mutation–to–phenotype correlation underscore the need for genetic testing. Significant relationships between age and worsening VA and GVF highlight the progressive loss of functional retina over time. These data may have implications for optimal timing of treatment for IRD attributable to biallelic RPE65 mutations.